A DEA-inspired model to evaluate the efficiency of education in OECD countries - Carlota Dominguez-Gil; Ignacio Contreras (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
In this paper empirical application to the study about the efficiency of the performance of the educational systems across countries is developed. With the information published in the PISA 2015, Data Envelopment Analysis methodology is considered to evaluate the efficiency in the use of the resources devoted to education by OECD countries. Similar to previous studies, the main resources needed for learning, financial, human resources, material and time have been considered. Alternatively to previous proposals, the mean scores have not been included as the output of the process. Instead of that, to quantify the results of the learning process, the percentages of students in each proficiency level of the PISA test have been computed.An ad hoc model based on the Additive DEA-model is proposed, adapting the formulation to the particular features of the vector of outputs considered. Considering that the aggregate value of output is fixed and that the relative weight of the outputs differs, inefficient units improve their performance by reallocating that fixed value among different outputs, moving units from the less valued to the most valued ones.
Keywords: I21; C61; 330; education; PISA; DEA